In silico sequence and structure prediction analysis of biomarker genes in Aeromonas sp. of Andaman and Nicobar Islands - Balakrishnan Meena; Lawrance Anburajan; Dilip Kumar Jha; Gopal Dharani (Emerging Contaminants, 2025)
The genus Aeromonas is considered as indigenous prokaryote to aquatic environments. These genus members are capable of colonizing in water bodies such as potable water, sewage and sea water. Aeromonas sp. is the most significant opportunistic pathogen in humans with the potential to cause different kinds of infections in blood, tissues, intestine, and dermis. The leading pathogenic species includes Aeromonas hydrophila, A. caviae and A. veronii. The ubiquitous nature in the environment associated with the virulence of these bacteria has been reported. Evidence for the waterborne transmission to humans by Aeromonas sp. is also documented. The Aeromonas found in wastewater and its impact on marine environment is hardly discussed and its bibliography is lacking. The aim of this research was to identify the major biomarker genes in Aeromonas sp., and it's in silico sequence analysis.